(untitled) (Research, Society and Development, 2022)
The objective of this study was to trace the social, economic, epidemiological and sports profile of basketball practitioners from the Rotary Court in the city of Montes Claros (MG). A total of 97 individuals participated in this study, 93 males and 4 females, aged between 12 and 45 years old, who played basketball in the square for at least 6 months. As a data collection instrument, face-to-face and online questionnaires were applied. As a result, it was found that the sample is dominated by males, the average age presented was 20.8 years and the average height presented was 1.81 (± 0.8) meters. Just over half of the sample does not have a job and has no monthly income, which contributes to the fact that the main means of transport for these individuals are walking and cycling. The data also show that 84.5% of the sample knew about basketball from the age of 12, and that 67% have been playing basketball for five years. Regarding the reason for practicing basketball, 52.6% declared playing for recreational purposes. Regarding epidemiological data, the sample had a mean BMI of 23.9 (± 4.1). Only 27 individuals had lesions. The results showed that variables such as weekly frequency and years of basketball practice are factors that may have contributed to the occurrence of these injuries. It is concluded that the Rotary Square contributes positively to the socioeconomic practice of basketball and the epidemiological factors for injuries may be training overloads and practice time.